Artykuł oryginalnyHeart rate variability in patients with recurrent syncope - Lelonek, Małgorzata; Goch, Jan Henryk (Archives of Medical Science, 2006)
Introduction: The autonomic nervous system participates in the pathophysiology of vasovagal syncope. The disturbances in the autonomic nervous system can be measured by heart rate variability (HRV). The aim of the study was to assess the usefulness of HRV spectral analysis during HUTT in patients with recurrent syncope. Material and methods: 170 patients with syncope were divided into: positive head-up tilt testing (HUTT) (group I) n=129 and negative HUTT (group II) n=41. The control group comprised 19 healthy volunteers. In all the history was taken, especially with data about syncope and coexisting diseases. Physical examination, 12-lead rest ECG, 24-hour Holter ECG and HRV spectral analysis during HUTT were also performed. Results: Analyzed groups differed in number of syncope, presence of prodromal symptoms (p<0.05) and typical vasovagal history (p<0.00000). In non-vasovagal patients there was significantly more hypertension, ventricular arrhythmia of IV b class pro Lown and conduction AV blocks (p<0.05). In all analyzed phases of HUTT there were significant differences of sympathetic and parasympathetic activity between vasovagal patients, non-vasovagal and controls. Changes of a component’s activity in the autonomic nervous system related to the tilting differentiated VASIS groups. Conclusions: HRV evidences disturbances of autonomic nervous system activity in patients with recurrent syncope. HRV spectral parameters at rest permit vasovagal patients to be separated from others suffering from syncope. HRV analysis requires further studies in patients with syncope.